2018
DOI: 10.1016/j.ihj.2018.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of asymptomatic ischemic heart disease using stress myocardial perfusion imaging in patients with type 2 diabetes mellitus

Abstract: BackgroundCoronary artery disease (CAD) is the leading cause of death in patients with type 2 diabetes mellitus (T2DM) and may be asymptomatic.ObjectiveThe objective of this study was to assess the prevalence of asymptomatic myocardial ischemia in patients with T2DM using stress myocardial perfusion imaging.MethodsWe evaluated 97 consecutive patients with T2DM without clinical evidence of CAD presenting to Cardiology and Endocrinology clinics using Tc-99m MIBI gated single-photon emission–computed tomography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Many techniques can be used to assess cardiac function, such as cardiovascular magnetic resonance T1 mapping [ 4 ], Tc-99 m MIBI gated single-photon emission-computed tomography myocardial perfusion imaging [ 5 ], tissue Doppler strain echocardiography [ 6 ], and two-dimensional speckle tracking echocardiography (2D-STE) [ 7 , 8 ]. However, these techniques all have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques can be used to assess cardiac function, such as cardiovascular magnetic resonance T1 mapping [ 4 ], Tc-99 m MIBI gated single-photon emission-computed tomography myocardial perfusion imaging [ 5 ], tissue Doppler strain echocardiography [ 6 ], and two-dimensional speckle tracking echocardiography (2D-STE) [ 7 , 8 ]. However, these techniques all have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…A contemporary study performed in India found a treadmill test positive for SMI in 23.1% out of 338 asymptomatic T2DM subjects [57], while another Indian study that enrolled 97 T2DM observed that only 10% out of the asymptomatic patients showed evidence of SMI or silent MI at SPECT [58]. Finally, a small Saudi Arabian study evaluating 59 T2DM patients without history of CAD, but with multiple CV risk factors detected an abnormal scan in 37% of the patients who had undergone myocardial perfusion SPECT imaging [59].…”
Section: Epidemiology Of Smimentioning
confidence: 98%
“…Evaluation of LV ESV provides added over LVEF alone for prediction of cardiac death [14]. Perfusion deficits are stronger predictors of MI occurrence than contractility impairments [14][15][16].…”
Section: Clinical and Research Value Of G-spect: Perfusion And Region...mentioning
confidence: 99%